1994
DOI: 10.1136/gut.35.6.783
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of amino acid v peptide based enteral diets in active Crohn's disease: clinical and nutritional outcome.

Abstract: Elemental diets are considered an effective primary treatment for active Crohn's disease. This study examined the hypothesis that improvement occurs because of the presence of amino acids or the low fat content, or both.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(47 citation statements)
references
References 21 publications
2
44
0
1
Order By: Relevance
“…After three weeks, clinical remission rates were similar in the amino acid group compared with the peptide group. The authors concluded that peptide-based diets are equally efficacious as amino acid-based diets in terms of high rates of clinical remission and is better tolerated orally [14] . In another randomized controlled study, Mansfield et al [15] compared the efficacy of a 100% WHP diet with an amino acid-based diet to achieve remission in 44 patients with active Crohn's disease.…”
Section: Crohn's Diseasementioning
confidence: 99%
See 3 more Smart Citations
“…After three weeks, clinical remission rates were similar in the amino acid group compared with the peptide group. The authors concluded that peptide-based diets are equally efficacious as amino acid-based diets in terms of high rates of clinical remission and is better tolerated orally [14] . In another randomized controlled study, Mansfield et al [15] compared the efficacy of a 100% WHP diet with an amino acid-based diet to achieve remission in 44 patients with active Crohn's disease.…”
Section: Crohn's Diseasementioning
confidence: 99%
“…10 -single group 6 wk Height increased 143.8 ± 13 to 144.5 ± 13.1 cm (P < 0.01) Weight increases 31.9 ± 7.2 to 36.5 ± 8.1 kg (P < 0.0001) PCDAI decrease 40 ± 13 to 5 ± 6 (P < 0.0001) (lower score corresponds to lower disease activity) Albumin increase 3.1 ± 0.4 to 3.8 ± 0.4 g/dL (P < 0.01) PEDIBDQ increase 198 ± 31 to 243 ± 34 (P < 0.01) (higher score indicating better quality of life) Royall et al [14] Adults with moderate to severely active CD RCT Peptamen administered via a nasoduodenal feeding tube (Vivonex-TEN, amino acid based formula) 21 (19) 3 wk Remission rates after 3 wk: 75% in the peptide group, 84% in the amino acid group Remission rates after 1 yr: 40% in the peptide group, 31% in the amino acid group Weight increased 2.0 ± 0.5 kg in the peptide group and 1.7 ± 0.3 kg in the amino acid group (P < 0.0005 within group differences after 3 wk) Total phospholipids (mg/mL) concentration increase in the peptide group (1.37 ± 0.1 to 1.71 ± 0.15) (P < 0.025) (no difference in amino acid group) Mansfield et al [15] Adults with active CD RCT Pepti-2000 LF Liquid received through nasogastric tube (Elemental 028)…”
Section: Feeding Durationmentioning
confidence: 99%
See 2 more Smart Citations
“…Poor nutritional status has been shown to be an independent risk factor for postoperative complications in patients with CD (3) . Nutritional support has been shown to improve clinical outcome in patients with CD (4) . In conclusion nutritional status should be frequently measured in patients with CD and nutritional support initiated at the earliest opportunity in those identified to be at risk of malnutrition with the aim of correcting nutritional deficiencies and improving clinical outcome.…”
mentioning
confidence: 99%